MENGGAGAS SINTESA GLOBAL-LOKAL DALAM MEMBANGUN HUKUM EKONOMI - Tri Budiono (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
Business paradigm has change. The newest business paradigm rooted on critical theory and postmodernism thinking. This condition should be accepted as a prerequisite condition for economic law to be developed. In the field of corporation law the government has enacted Corporation Act in 1995 (Act No. 1, 1995). According to the Corporation Act, there are many doctrines which were transplanted from common law traditions into Indonesian Corporation Act which applied in a civil law traditions. From this point of view, many problems arose especially on how those doctrines should be implemented. This articles try to discuss this problem.